Analysis of Teachers' Professional Competencies in Writing Scientific Articles Based on Class Action Research (PTK) Through The Participatory Action Research (PAR) Method - Erika Mei Budiarti; Suwandi Suwandi; Asep Kurniawan; Desi Eri Kusumaningrum (Universitas Negeri Malang, 2025)
Abstract: The purpose of the research designed was to describe teacher competence in writing scientific papers based on Classroom Action Research (PTK) articles which can be published in electronic journals. This research was conducted at SDIT Ar Ruhul Jadid with a sample design of 70 respondents, but the data obtained by researchers was 42 respondents. Researchers used 2 methods which were carried out simultaneously, namely action research and descriptive quantitative. There are several achievement indicators that researchers want to explore in this study, including respondents' understanding of the Participatory Action Research (PAR) method; understanding related to scientific work; Furthermore, Classroom Action Research (PTK) is part of scientific work; as well as understanding regarding the Open Journal System (OJS) from the respondents. More complex research results can be seen in this article. Keywords: scientific articles; Participatory Action Research (PAR); teacher professional competence